Analysis of the bathing suitability of the beaches of Itanhaém (São Paulo, Brazil): insights from a long-term monitoring data series (Research, Society and Development, 2022)
The quality of beach water in coastal cities is essential for public health. The concept of bathing is applied when there is prolonged and direct human contact with water and where there is the possibility of ingestion, such as at beaches.  Therefore, it is important to understand the bathing suitability of the coastal beaches both as a health issue and for the tourism industry. The municipality of Itanhaém, the object of the study, is located on the southern coast of the state of São Paulo, in the Metropolitan Region of Baixada Santista. The objective of this research was to analyze the bathing conditions of twelve beaches in the municipality of Itanhaém -SP-Brazil, in relation to the water bodies that reach the beaches, and the sanitation conditions, between 2010 and 2020. For this, secondary data made available by the Environmental Company of the State of São Paulo were used. Most beaches in Itanhaém-SP have annual values of bathing considered regular, in the period studied. An improvement in the water quality of the bodies of water that reach these beaches was observed, which may be a reflection of the increase in the number of households with sewage collection. It is expected that with the improvement of sanitation services, the beaches will become safer for tourists and residents of the municipality.